Bacon's Ideas in his Essays: A Study from the Perspective of Islam - Kabir, Mohammad Humayun (IIUC Studies, 2009)
The paper aims at examining Francis Baconâs ideas in his Essays from the point of view of Islam. Taking some representative essays of Francis Bacon, I have tried to find out those ideas in these essays which are conflicting with Islamic ideas. Here I have also identified some baseless statements of bacon about our Prophet Mohammad (SM) and the Muslim ummah and Baconâs allegation against Hazrat Mohammad (SM) has also been refuted. A threadbare analysis of Baconâs ideas as revealed in the Essays has been done in the light of the Holy Quran. Here it is also discussed how Baconian ideas are harmful to mankind and for human civilization in general. doi: IIUC Studies Vol.2 2004